Ground improvement techniques - Patra, Nihar Ranjan (Vikas Publishing House, 2012)
Ground improvement techniques / Patra, Nihar Ranjan. -- Kolkata: Vikas Publishing House, 2012 624.1513 P314 No. of Copies : 1